Computational Investigation: CFD guide for the Evaporation process in Heat Pipe - Далал Ахмед; Раїд Махмуд (Mechanics and Advanced Technologies)
Heat pipes are crucial in various industrial applications owing to their superior heat transfer properties and their improvement of thermal management systems. This work introduces a two-dimensional Computational Fluid Dynamics (CFD) simulation to examine the temperature distribution and phase change processes occurring during evaporation in a heat pipe. ANSYS Fluent is employed to create the 2D heat pipe shape and produce an optimal computational mesh. A k-ɛ turbulence model is utilized to characterize fluid flow behavior, and nanorefrigerant (Al2O3/R11) is designated as the working fluid. Simulation results indicate a substantial temperature differential in the evaporator portion, as well as the impact of heat flow and wick construction on thermal resistance. The CFD results offer significant insights for optimizing heat pipe design and a comprehensive comprehension of the evaporation process, which is a consequence of phase change.